Perception of Self and Safe Sexual Behavior among Fresh, Undergraduates in a Nigerian University (2000)
Descriptive as well as interventional studies regarding sexual activity, vis a vis safe sexual practice among adolescents and young adults have found that many of these youths are still particularly permissive in their sexual behavior, despite numerous behavioral approach suggested for its prevention and minimization. Pre-morbid personality characteristics .of the individual youths have been asserted by contemporary researchers to play a part in adherence to this safe sexual practice. This study was designed to examine the effect of self-efficacy, self-esteem, age, gender as well as years of education as they affect and related to safe sex-behavior among fresh University Undergraduates. 200 fresh University Undergraduates of University of Ibadan were used. They comprised of 124 males and 76 females. The mean age was 21.75 (SD, 3.33). The mean for years of education was 13.37 (SD 2.48). Using instruments to assess self-efficacy, self esteem, demographic data and safe sexual behavior. Results indicated that fresh University undergraduates with high level of self efficacy and self-esteem would engaged in safe sex behavior. Also found was the relationship between increasing, age and years of education to safe sexual behavior. Results were discussed in relation to existing literature and theories on safe sexual practice.